Pengendalian Kehilangan Minyak Di Final Effluent Menggunakan Metode Statistical Quality Control Pada Proses Pengolahan Crude Palm Oil PT XYZ - Firdaus, Muhammad Reza; Lestari, Ema; Fatimah, Fatimah; Chalid, Sihabuddin (Jurnal Teknologi Agro-Industri, 2024)
PT XYZ is an agro-industrial company that focuses on palm oil processing, mainly producing Crude Palm Oil (CPO) and kernels. The main process carried out by the company is processing fresh fruit bunches (FFB) into CPO and palm kernel (kernel). The level of oil losses in PT's final effluent. XYZ should not exceed 0.40%, but in 3 months, there has been an increase that exceeds the company's standards. This condition can affect CPO production results. Therefore, this research was conducted to analyze oil loss in the final effluent. The method used is Statistical Quality Control (SQC) using three tools, namely Check Sheet to collect data, Histogram to show data distribution, and cause-and-effect diagram to assist in understanding and solving the problems faced. The research results showed that oil loss was the highest, 0.57% in October, 0.46% in November, and 0.45% in December 2023. Therefore, it is necessary to make recommendations for improvements using a cause and effect diagram that includes machine, human and method factors to meet the desired standards, factors that cause high oil losses including lack of attention to equipment maintenance, inconsistent machine cleaning times and overlooked oil citing momentum.